KONSEP SPASIAL LAMIN ADAT SUKU DAYAK KENYAH DI KABUPATEN KUTAI KARTANEGARA - , RUSFINA WIDAYATI, ST, Dr. Ir. A. Sarwadi. M. Eng ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Lamin (long house), is Dayak traditional house, have been known as one of unique architecture in east Borneo, especially in Kutai Kartanegara county. Lamin (long house), as a living houses not only physical formation but also as community system, so lamin as communal living houses. The migration caused Lamin ( long house) is abandoned. The reason are, health problems